2022
DOI: 10.1111/jce.15599
|View full text |Cite
|
Sign up to set email alerts
|

Differences in outcomes among patients with atrial fibrillation undergoing catheter ablation with versus without intracardiac echocardiography

Abstract: Background Intracardiac echocardiography (ICE) use can lead to early detection of periprocedural complications and may improve patient outcomes by providing real‐time visualization of catheter location and the treatment area during cardiac ablation (CA) for atrial fibrillation (AF). Objective Examine complications and 12‐month healthcare use among patients with AF undergoing CA with versus without ICE use during the procedure in a real‐world setting. Methods The 2015–2020 IBM MarketScan® Database was used to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…The impact of ICE on the incidence of TSC complications was not significant in a study by Swedish authors on 4690 procedures; however, it was used only in 0.5% of cases [ 14 ]. Our results, moreover, are in agreement with the data of previous series [ 9 , 13 , 15 ] and a large recently published US registry [ 7 ] on patients undergoing AF ablation that showed a significant reduction in periprocedural complications, in-hospital mortality and hospital stay in the ICE group, at the expense of a significant increase in costs. The shorter hospitalization times, according to the authors, were, however, able to make the procedure with ICE cost-effective.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The impact of ICE on the incidence of TSC complications was not significant in a study by Swedish authors on 4690 procedures; however, it was used only in 0.5% of cases [ 14 ]. Our results, moreover, are in agreement with the data of previous series [ 9 , 13 , 15 ] and a large recently published US registry [ 7 ] on patients undergoing AF ablation that showed a significant reduction in periprocedural complications, in-hospital mortality and hospital stay in the ICE group, at the expense of a significant increase in costs. The shorter hospitalization times, according to the authors, were, however, able to make the procedure with ICE cost-effective.…”
Section: Discussionsupporting
confidence: 92%
“…The rate of periprocedural complications in the study population was 3.1%, in line with previous studies, and, in particular, was 1.7% in the ICE group and 4.7% in the no ICE group. Recently, Pimentel et al reported in a series of more than 2000 patients a rate of complications that was 2.9% in the ICE group and 5.8% in the no ICE group, which is in line with our results [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…There is a paucity of trials specifically examining the role of ICE in ablation procedures. Two large observational studies suggest ICE use in RF ablation is associated with a significant decrease in procedural complications, lower in‐hospital mortality, and shorter hospital length of stay but higher procedural cost 7,8 . A recent randomized trial examining the feasibility of ICE‐guided CBA without fluoroscopy demonstrated significantly decreased radiation with similar success rates and no difference in complications 9 .…”
mentioning
confidence: 99%
“…(2) facilitating catheter positioning (particularly, circular mapping catheters within fluoroscopically invisible pulmonary vein antra), (3) detecting RF-induced microbubble showers and left atrial appendage/ catheter thrombi (potentially reducing the risk of stroke), (4) identifying early pericardial effusions (before rapid progression to life-threatening tamponade), (5) avoiding RF delivery near the esophagus (decreasing development of atrio-esophageal fistulae), ( 6) evaluating for pulmonary vein stenosis (by pulsed flow velocities and color Doppler), and (7) minimizing fluoroscopy. 2,3 However, ICE is not universally available and single use, nonreprocessed catheters are expensive (~$2500 for phased-array ICE, ~$1100 for rotational ICE which also requires a separate ultrasound processing console).…”
mentioning
confidence: 99%
“…2,5,6 But what about real world practice? In this issue, Pimentel et al 7 used a large insurance claims database to compare 1371 nonelderly patients who underwent AF ablation without ICE between 2016 and 2020 (7.1% of total AF ablation patients) to a propensity matched cohort undergoing AF ablation with ICE. They found that the ICE cohort had a significantly lower rate of complications (2.9 vs. 5.8%, p < .001; 50% lower risk) and a significantly lower need for repeat ablation at 12 months (7.4% vs. 11.5%, p = .001; 36% lower risk).…”
mentioning
confidence: 99%